A socio-technical negotiation approach for collaborative design in software engineering. (27th July 2009) - Lu, Stephen C-Y.; Jing, Nan
To support collaborative design in software engineering, we have built a socio-technical negotiation approach by integrating a Socio-Technical Co-construction Process (STCP) with an Argument-Based Negotiation Process (ABNP). The STCP provides rich contextual information of technical decisions and social interactions in a software design process. The ABNP provides STCP with a conflict resolution strategy by guiding software engineers to generate, exchange and evaluate their argument claims in negotiation activities. This paper reviews relevant research work and presents each step of this negotiation approach. In addition, this paper describes a prototype system which implements this new approach using the advanced web-based software technologies with the goal of demonstrating the enhanced negotiation capabilities in a dynamic socio-technical framework.